The Implication, Characteristics and Significance of the Chinese Unique Educationalist Spirit - TAN Tianmei; HU Jinxia (Jiaoshi jiaoyu xuebao)
The relevant discussion on the Chinese unique educationalist spirit profoundly answers the important questions of why to carry forward the educationalist spirit, what kind of educationalist spirit to carry forward and how to carry forward the educationalist spirit. It highlights the distinctive people-oriented, scientific, practical, and national characteristics, which contain the people's position of "preaching for the people and teaching for the people", carries the scientific core of "radical reform and innovation", highlights the practical goal of "educating people for the Party and the country", and has the national root of "advocating morality and respecting teachers and education". The discussion of the Chinese unique educationalist spirit has both theoretical and practical guiding significance for promoting the theoretical innovation of the teacher education system with Chinese characteristics, boosting the self-confidence of high-quality professional teachers and enhancing the global influence of teacher education discipline construction.